2021
DOI: 10.1117/1.nph.8.2.025003
|View full text |Cite
|
Sign up to set email alerts
|

Implantable photonic neural probes for light-sheet fluorescence brain imaging

Abstract: . Significance: Light-sheet fluorescence microscopy (LSFM) is a powerful technique for high-speed volumetric functional imaging. However, in typical light-sheet microscopes, the illumination and collection optics impose significant constraints upon the imaging of non-transparent brain tissues. We demonstrate that these constraints can be surmounted using a new class of implantable photonic neural probes. Aim: Mass manufacturable, silicon-based light-sheet photoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…However, if one were to perform chip thinning before the integration step of the soft substrate with the more rigid electronics, the risk of damage to the neural probe could be attenuated. In fact, a study performed by Sacher et al [66] demonstrated that back grinding could be a suitable chip thinning method for photonic neural probes with a thickness ranging from 50-92 µm. In addition to this, there have been techniques explored to reduce mechanical damage to the chips caused by back grinding, such as the one explored by Morcom et al [67], known as taiko, where grinding is not performed on the periphery of the back, non-active side of the wafer, leaving a ring structure that enhances the structural integrity of the wafer.…”
Section: Chip Thinning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if one were to perform chip thinning before the integration step of the soft substrate with the more rigid electronics, the risk of damage to the neural probe could be attenuated. In fact, a study performed by Sacher et al [66] demonstrated that back grinding could be a suitable chip thinning method for photonic neural probes with a thickness ranging from 50-92 µm. In addition to this, there have been techniques explored to reduce mechanical damage to the chips caused by back grinding, such as the one explored by Morcom et al [67], known as taiko, where grinding is not performed on the periphery of the back, non-active side of the wafer, leaving a ring structure that enhances the structural integrity of the wafer.…”
Section: Chip Thinning Methodsmentioning
confidence: 99%
“…In fact, a study performed by Sacher et al . [ 66 ] demonstrated that back grinding could be a suitable chip thinning method for photonic neural probes with a thickness ranging from 50–92 µm. In addition to this, there have been techniques explored to reduce mechanical damage to the chips caused by back grinding, such as the one explored by Morcom et al .…”
Section: Chip Thinning Methodsmentioning
confidence: 99%
“…On this topic, focused on the importance of nano-optics for targeted biosignals in tissues and real samples, the development of implantable photonic neural probes for light-sheet fluorescence brain imaging has recently been reported. 69 This imaging approach was successfully achieved by the use of a miniaturized optical setup along with the incorporation of a probe with a propagation capability of distances up to 300 μm in free space using fluorescent optical responsive beads suspended in agarose as medium. The different steps involved in the design and several lithography and surface modification techniques should also be mentioned.…”
Section: Current Trends and Future Perspectives Of Implantable Portab...mentioning
confidence: 99%
“…Implantable silicon photonic light delivery probes have also been used for fluorescence imaging [93,94]. For example, Sacher et al developed implantable probes to generate light-sheets deep in scattering tissues and demonstrated in vitro and in vivo fluorescence imaging of mouse brains [93]. For quantum information processing, the SiN platform can offer a scalable and robust light delivery system for trapped ion qubits.…”
Section: Other Emerging Free-space Applicationsmentioning
confidence: 99%
“…To study the brain circuitry, it is important to deliver light precisely to a small population of neurons deep in the brain. Silicon photonics can provide an implantable, precise, switchable light delivery system [ 17 , 92 , 93 , 94 ]. Mohanty et al demonstrated an implantable reconfigurable probe based on the SiN platform [ 17 ], as shown in Figure 13 a.…”
Section: Other Emerging Free-space Applicationsmentioning
confidence: 99%